Malignant ovarian germ cell tumors in pediatric patients: The AIEOP (Associazione Italiana Ematologia Oncologia Pediatrica) study. Issue 11 (27th April 2017) - Terenziani, M.; Bisogno, G.; Boldrini, R.; Cecchetto, G.; Conte, M.; Boschetti, L.; De Pasquale, M.D.; Biasoni, D.; Inserra, A.; Siracusa, F.; Basso, M.E.; De Leonardis, F.; et al.
Abstract: Objective: Malignant ovarian germ cell tumors (MOGCT) carry an excellent prognosis, and the treatment aims to achieve results with the least possible treatment‐related morbidity. The aim of this study was to assess the outcomes of pediatric patients with MOGCT. Methods: Patients were treated according to their stage: surgery and surveillance for stage I; a modified bleomycin–etoposide–cisplatin (BEP) regimen for stages II (three cycles), III, and IV (three cycles) with surgery on residual disease. Results: Seventy‐seven patients were enrolled (median age 11.8 years), 26 with dysgerminoma (Dysg), 13 with immature teratoma and elevated serum alpha‐fetoprotein levels (IT + AFP), and 38 with nondysgeminoma (Non‐Dysg) staged as follows: 27 stage I, 13 stage II, 32 stage III, 5 stage IV. Among evaluable patients in stage I (5‐year event‐free survival [EFS] 72.1% [95% CI: 56.4–92.1%]; 5‐year overall survival [OS] 100%), seven relapsed (three patients with Dysg and four patients with Non‐Dysg) and were rescued with chemotherapy (plus surgery in three patients). Among the evaluable patients with stages II–IV, 48 (98%) achieved complete remission after chemotherapy ± surgery, one (IT + AFP, stage IV) had progressive disease. In the whole series (median follow‐up 80 months), the 5‐year OS and EFS were 98.5% (95% CI: 95.6–100%) and 84.5% (95% CI: 76.5–93.5%). Conclusions: We confirm the excellent outcome for MOGCT. Robust data are lacking on surgical staging, surveillance for Non‐Dysg with stage I, the management of IT + AFP, and the most appropriate BEP regimen. As pediatric oncologists, we support the role of surveillance after proper surgical staging providing cases are managed by experts at specialized pediatric centers.